2017
DOI: 10.1200/jco.2017.35.31_suppl.180
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality among Latino caregivers of patients with advanced cancer: A qualitative study.

Abstract: 180 Background: Caregivers of cancer patients often face significant physical, social, and emotional distress. There has been limited research on the association between Latino Caregivers’ spirituality/religiosity, meaning, and spiritual pain. Methods: We interviewed 336 Latino Caregivers of patients at Palliative Care clinics in Chile, Guatemala, and the US. Five open-ended questions were asked about spirituality, religion, meaning, and spiritual pain. Answers were transcribed and data analyzed. The analytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…28 Spirituality has also been described as an anchor during the cancer caregiving experience for individuals who are Latino, with both internal and organizational spirituality resulting in lower perceived caregiver burden. 29,30 Latina individuals with breast cancer have described selecting caregivers on the basis of their religious beliefs. 31 Research has shown an inverse relationship between religious practice and life expectancy, although religious doubts or struggles, congregational criticism, or negative interpersonal religious experiences all may affect health adversely.…”
Section: Spiritual Practicementioning
confidence: 99%
See 1 more Smart Citation
“…28 Spirituality has also been described as an anchor during the cancer caregiving experience for individuals who are Latino, with both internal and organizational spirituality resulting in lower perceived caregiver burden. 29,30 Latina individuals with breast cancer have described selecting caregivers on the basis of their religious beliefs. 31 Research has shown an inverse relationship between religious practice and life expectancy, although religious doubts or struggles, congregational criticism, or negative interpersonal religious experiences all may affect health adversely.…”
Section: Spiritual Practicementioning
confidence: 99%
“…This idea has been noted in a qualitative study, with caregivers describing the connection between their spiritual practice and family 28 . Spirituality has also been described as an anchor during the cancer caregiving experience for individuals who are Latino, with both internal and organizational spirituality resulting in lower perceived caregiver burden 29,30 . Latina individuals with breast cancer have described selecting caregivers on the basis of their religious beliefs 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Como se mencionó anteriormente existe evidencia de que la espiritualidad, religiosidad y el dolor espiritual pueden influir en la angustia de los síntomas, la calidad de vida y las estrategias de afrontamiento de las personas con enfermedades avanzadas y terminales, y que pueden utilizarse como terapia integradora para promover el bienestar y la salud en general 11 . La presente revisión narrativa presenta un análisis de la observación a la espiritualidad desde la mirada de la TO en el contexto de los Cuidados Paliativos.…”
unclassified